Phylogenetic analysis of ORF viruses from five contagious ecthyma outbreaks in Argentinian goats - Peralta, Andrea Veronica; Robles, Carlos Alejandro; Micheloud, Juan Francisco; Rossanigo, Carlos Esteban; Martinez, Agustin; Carosio, Agustin; Konig, Guido Alberto (2018)
Orf virus (ORFV) is the etiological agent of Contagious Ecthyma (CE) disease that mainly affects sheep, goats, wild ruminants, and humans with a worldwide distribution. To date, only two strains from Argentinian sheep have been characterized at the molecular level and there is little information on ORFV strains circulating in Argentina. Here we describe and analyze five outbreaks of CE in goats in three geographic regions of the country: Northwest, Center, and Southwest. The phylogenetic analysis based on four molecular markers of ORFV (orf011 partial sequence and orf020, orf109, and orf127 complete sequence genes) revealed that there are different strains circulating in Argentina and pointed out the importance of knowing the health status of animals traded between farms.